Task-oriented methodology for objective assessment hand rehabilitation with robotics therapy - Huang, YunYun (2013)
Impairments such as muscle weakness, loss of range of motion, decreased reaction times and disordered movement organization create deficits in motor control, which affect independent living of patients. Rehabilitation robotic systems are then suggested to help the patients in maintaining or improving their independence and to reduce the burden of care on institutions and caregivers.